Thirty-day readmission after endovascular or surgical revascularization for chronic mesenteric ischemia: Insights from the Nationwide Readmissions Database. (June 2019) - Lima, Fabio V; Kolte, Dhaval; Louis, David W; Kennedy, Kevin F; Abbott, J Dawn; Soukas, Peter A; Hyder, Omar N; Mamdani, Shafiq T; Aronow, Herbert D
There are limited contemporary data on readmission after revascularization for chronic mesenteric ischemia (CMI). This study aimed to determine the rates, reasons, predictors, and costs of 30-day readmission after endovascular or surgical revascularization for CMI. Patients with CMI discharged after endovascular or surgical revascularization during 2013 to 2014 were identified from the Nationwide Readmissions Database. The rates, reasons, length of stay, and costs of 30-day all-cause, non-elective, readmission were determined using weighted national estimates. Independent predictors of 30-day readmission were determined using hierarchical logistic regression. Among 4671 patients with CMI who underwent mesenteric revascularization, 19.5% were readmitted within 30 days after discharge at a median time of 10 days. More than 25% of readmissions were for cardiovascular or cerebrovascular conditions, most of which were for peripheral or visceral atherosclerosis and congestive heart failure. Independent predictors of 30-day readmission included non-elective index admission, chronic kidney disease (CKD), and discharge to home healthcare or to a skilled nursing facility. Revascularization modality did not independently predict readmission. In a nationwide, retrospective analysis of patients with CMI undergoing revascularization, approximately one in five were readmitted within 30 days. Predictors were largely non-modifiable and included non-elective index admission, CKD, and discharge disposition.